DI-016 Regional card for the prescription of botulinum toxin by Clostridium Botulinum type A: an instrument for appropriate prescribing. (24th February 2014) - Caldarini, S; Altavista, MC; Balestreri, A; Di mattia, MG; Ferraro, A; Iovino, A; Paglia, L; Pagliaro, R; Pisanelli, C; Santarelli, M; Tufo, A; Zaccaro, G
Abstract : Background: Three medicinal products containing botulinum neurotoxin type A (BT), ATC M03AX1, are currently available in the market. All BT preparations are of biological origin, and they are differentiated by the cell strain or the batch of Clostridium botulinum from which the cell culture originates, and by the purification process. This implies that the BT formulations have different pharmacokinetic and pharmacodynamic characteristics; therefore they must be considered as originator biological preparations, and then not overlapping or interchangeable. Purpose: Our goal has been to ensure and verify the appropriate prescription of BT. Materials and methods: The Lazio Region has developed a regional card for prescription of BT in compliance with the approved therapeutic indications (Table 1 ). After verifying the appropriateness and suitability of the regional boards, the BT is delivered and cards processed and entered into an Access database. The period covered is the year 2012. Results: During the period of analysis 721 cards were prepared, for a total of 213 patients: a single case of incobotulinumtoxinA inappropriate prescribing was detected in the treatment of hemifacial spasm. From our study, it was found that 31 patients treated with therapeutic onabotulinumtoxinA had a switch, of which 19 to incobotulinumtoxinA and 12 to abobotulinumtoxinA. One patient being treated with incobotulinumtoxinA had a therapeutic switch to abobotulinumtoxinA. Conclusions: The future goal is to verify what rational therapeutic switches were made in consideration of the interchangeability of BT and to clarify the proper application of law 648/96 in the neurological area, all in order to guide the physician to ever more appropriate prescribing. No conflict of interest.